Robust Motion Modification for Robot Manipulators in Constrained Environments - Muslu, Batin; Oztoprak, Burak; Baran, Eray A.; Sabanovic, Asif (IEEE, 2018)
This paper presents a controller structure for the continuous and robust modification of motion for multi body systems encountering contact with an environment during free motion. The presented algorithm relies on the reformulation of the position tracking error with a term proportional to the reaction force. With the proposed method, fusion of the position and the force controllers can be achieved which provide the robot with certain level of compliance. The derivation of the proposed method is followed by experiments made on a pantograph mechanism actuated by direct drive linear motors. The results obtained from the experiments illustrate the success of the proposed control architecture in providing a natural behavior for the robotic systems working in constrained environments.
6th International Conference on Control Engineering and Information Technology (CEIT) -- OCT 25-27, 2018 -- Istanbul, TURKEY
Keywords: Motion Modification; Constrained Motion Control; Force Control; Hybrid Control; Disturbance-Observer; Position Control; Force Control; Validation